A Polish Pilot Programme of Coordinated Care: A Herald of Change or a Missed Opportunity? A Critical Debate - Karasiewicz, Monika; Chawłowska, Ewelina M.; Lipiak, Agnieszka; Staszewski, Rafał (Frontiers in Public Health, 2020)
The part of the health system which is essential for achieving universal health coverage is primary health care. Recognising the need to reform the health system and primary care in particular, on 1 July 2018 the Polish government launched POZ Plus—a pilot programme of coordinated primary care. Its objectives are to improve the quality and coordination of care and to expand its scope. The objectives are to be delivered through preventive health checks in patients aged 20–65 years, predefined chronic disease management programmes, as well as coordination and monitoring of care carried out by primary care teams. The programme provoked a heated debate and mixed reactions from different stakeholders in Poland. On the positive side, POZ Plus improves patient experience and seems to be a promising preventive tool. During the first 14 months of programme life, 10,956 health checks resulted in 13,361 new diagnoses. The critics of the programme point out that the scope of care is too wide and unnecessary in general population, and the health checks are too long, given the scarcity of medical professionals in Poland. The programme requires significant up-front investment of time and resources, thus favouring big clinics from densely populated areas. Financing may be sufficient during the pilot phase, but the programme may turn out to be too costly for country-wide implementation. The programme is a promising start toward achieving better primary care coordination in Poland. However, its success is conditional on sound public financing, rational workforce strategy, and close collaboration of all stakeholders.